2015
DOI: 10.1021/acs.langmuir.5b00196
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Cell Entrapment as a Function of the Weight Percent of Peptide-Amphiphile Hydrogels

Abstract: The design of scaffolds which mimic the stiffness, nanofiber structure, and biochemistry of the native extra-cellular matrix (ECM) has been a major objective for the tissue engineering field. Furthermore, mimicking the innate three dimensional (3D) environment of the ECM has been shown to significantly alter cellular response compared to traditional two dimensional (2D) culture. We report the development of a self-assembling, fibronectin-mimetic, peptide-amphiphile nanofiber scaffold for 3D cell culture. To fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…There was no statistically significant difference between these two measurements, and therefore the entrapment of iPSCs in the Cell‐Mate3D gels had no effect on the mechanical properties of the gels. A decrease in the Young's modulus of a hydrogel after entrapment of cells has been previously demonstrated and was attributed to embedding cells that are softer than the gel and the disruption of interactions between the gel fibers [29]. Interestingly, Engler et al showed that mesenchymal stem cells differentiate to a neural lineage on a substrate stiffness of 0.1–1 kPa [26], and Leipzig and Shoichet showed that neural stem/progenitor cells will differentiate to neurons, astrocytes, and oligodendrocytes when cultured on substrates of stiffness between 0.6 and 7 kPa, whereas on stiffer substrates (≥10 kPa), they will differentiate to oligodendrocytes [30].…”
Section: Discussionmentioning
confidence: 99%
“…There was no statistically significant difference between these two measurements, and therefore the entrapment of iPSCs in the Cell‐Mate3D gels had no effect on the mechanical properties of the gels. A decrease in the Young's modulus of a hydrogel after entrapment of cells has been previously demonstrated and was attributed to embedding cells that are softer than the gel and the disruption of interactions between the gel fibers [29]. Interestingly, Engler et al showed that mesenchymal stem cells differentiate to a neural lineage on a substrate stiffness of 0.1–1 kPa [26], and Leipzig and Shoichet showed that neural stem/progenitor cells will differentiate to neurons, astrocytes, and oligodendrocytes when cultured on substrates of stiffness between 0.6 and 7 kPa, whereas on stiffer substrates (≥10 kPa), they will differentiate to oligodendrocytes [30].…”
Section: Discussionmentioning
confidence: 99%
“…PR_g peptide amphiphiles were diluted with another peptide, C 16 -GGGSSSESE (E 2 ), to screen charges and enable faster gelation. PR_g/E2 gels supported 3D culture and proliferation of fibroblasts (NIH3T3/GFP) over five days [53]. In seminal work, Stupp and coworkers designed another peptide amphiphile (PA) that contained a 16-carbon chain, 4 alanine residues, 3 glycine residues, and the sequence IKVAV, which is found in laminin and known to promote and direct neurite outgrowth.…”
Section: Chemistries To Form and Modify Hydrogelsmentioning
confidence: 99%
“…[30,31,45] Recently, peptide amphiphile hydrogels have been explored for this need due to their design flexibility, ease of synthesis, and similarity to natural ECM of cartilage. [33] PA hydrogels were successfully used in encapsulation processes for different cell types such as MC3T3-E1, [32,46] neural progenitor cells, [47] fibroblasts, [48] hBMSCs. [38] However, they have never been studied in detail for building cartilage layer of an osteochondral scaffold or an osteochondral system composed of multiple cell types in different layers.…”
Section: Pa-rgds Hydrogel As Cartilage Sidementioning
confidence: 99%